Automated x‐ray/light field congruence using the LINAC EPID panel. Issue 3 (1st March 2013) - Polak, Wojciech; O'Doherty, Jim; Jones, Matt
Abstract : Purpose: : X‐ray/light field alignment is a test described in many guidelines for the routine quality control of clinical linear accelerators (LINAC). Currently, the gold standard method for measuring alignment is through utilization of radiographic film. However, many modern LINACs are equipped with an electronic portal imaging device (EPID) that may be used to perform this test and thus subsequently reducing overall cost, processing, and analysis time, removing operator dependency and the requirement to sustain the departmental film processor. Methods: : This work describes a novel method of utilizing the EPID together with a custom inhouse designed jig and automatic image processing software allowing measurement of the light field size, x‐ray field size, and congruence between them. The authors present results of testing the method for aS1000 and aS500 Varian EPID detectors for six LINACs at a range of energies (6, 10, and 15 MV) in comparison with the results obtained from the use of radiographic film. Results: : Reproducibility of the software in fully automatic operation under a range of operating conditions for a single image showed a congruence of 0.01 cm with a coefficient of variation of 0. Slight variation in congruence repeatability was noted through semiautomatic processing by four independent operators due to manual marking of positions on the jig. Testing of the methodology using the automatic method shows a high precision of 0.02 mm compared to a maximum of 0.06 mm determined by film processing. Intraindividual examination of operator measurements of congruence was shown to vary as much as 0.75 mm. Similar congruence measurements of 0.02 mm were also determined for a lower resolution EPID (aS500 model), after rescaling of the image to the aS1000 image size. Conclusions: : The designed methodology was proven to be time efficient, cost effective, and at least as accurate as using the gold standard radiographic film. Additionally, congruence testing can be easily performed for all four cardinal gantry angles which can be difficult when using radiographic film. Therefore, the authors propose it can be used as an alternative to the radiographic film method allowing decommissioning of the film processor.